RENAL HEMODYNAMICS AND GLOMERULAR FILTRATION RATE IN MEN AND WOMEN WITH ARTERIAL HYPERTENSION AT THE AGE OF 40-60 YEARS - I. G. Fomina; A. E. Bragina; N. E. Gaydamakina; J. N. Salimzhanova (Рациональная фармакотерапия в кардиологии)
Aim. To study parameters of a renal hemodynamic and the general glomerular filtration rate (GGFR) and their correlations with cardiovascular risk factors (RF) in patient with arterial hypertension (AH).Material and methods. 102 patients with AH (35 men and 67 women of 40-60 y.o.) were involved in the study. 20 persons (10 men and 10 women) with normal blood pressure (BP) were included in control group. Dynamic renal angioscintigraphy was used for an estimation of a renal hemodynamic and GGFR.Results. Hypertensive women had lower renal blood flow and GGFR than these in men (p<0,000). Renal hemodynamics and GGFR in men and women did not differ in control group. Positive correlation  r=0,61; p<0,05) between GGFR and a tobacco smoking was found in hypertensive men as well as negative correlation (r=-0,41; p<0,005) between GGFR and body mass index (BMI) in women.Conclusion. Renal blood flow and GGFR are lower in hypertensive women than these in men. Positive correlation between GGFR and tobacco smoking and negative correlation between GGFR and BMI were found in men and women respectively.